Emerging Evidence on Vouchers and Faith-based Providers in Education : Case Studies from Africa, Latin America, and Asia - Barrera-Osorio, Felipe; Patrinos, Harry Anthony; Wodon, Quentin (World Bank, 2012)
The case studies in this book provide useful information on the characteristics of students and the performance of various types of schools that benefit from public-private partnerships. While these case studies are empirically grounded, their results are not necessarily of universal application, because context also matters. The authors are careful to point out that while one of the case studies is based on an experiment, the other case studies use instruments or matching methods that have their limitations. Yet a key result from this work is that sound analyses of existing data are feasible and can yield useful conclusions about the contribution that private service providers can offer to educational development. These case studies will encourage more researchers to undertake similar work to demonstrate the many options that developing countries have to reach their education goals.